2010
DOI: 10.3354/meps08428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the heterotrophic dinoflagellate Oxyrrhis marina and the copepod Acartia tonsa on vertical carbon flux in and around thin layers of the phytoflagellate Isochrysis galbana

Abstract: Dynamics of material and energy flow through food webs differ when resources are allocated in patches in comparison to situations in which the same resources are distributed evenly throughout the water column. Thin layers of plankton are special cases of such resource patches. While previous studies have predominantly focused on the response of organisms to these layers, we investigated how 2 types of grazers in turn affect thin layers. In an experimental study with tightly controlled environmental conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…MendenDeuer & Lessard 2000). Since its invention, the radioisotope method has been effectively applied to measure phototrophic processes, including phytoplankton growth rates and carbon to chlorophyll a (chl a) ratios (Welschmeyer & Lorenzen 1984), heterotrophic protist grazing rates (Montagnes & Les sard 1999), release of organic matter (Bochdansky et al 2010), and cellular carbon content (Putt & Stoe cker 1989, Crawford & Stoecker 1996.…”
Section: Abstract: Photosynthesis−irradiance Relationship · Patchinementioning
confidence: 99%
“…MendenDeuer & Lessard 2000). Since its invention, the radioisotope method has been effectively applied to measure phototrophic processes, including phytoplankton growth rates and carbon to chlorophyll a (chl a) ratios (Welschmeyer & Lorenzen 1984), heterotrophic protist grazing rates (Montagnes & Les sard 1999), release of organic matter (Bochdansky et al 2010), and cellular carbon content (Putt & Stoe cker 1989, Crawford & Stoecker 1996.…”
Section: Abstract: Photosynthesis−irradiance Relationship · Patchinementioning
confidence: 99%
“…Some species of marine zooplankton vertically colocate with maxima in their phytoplankton food, while others do not (Dagg et al 1989;Pierson et al 2005;Rollwagen-Bollens et al 2006). So-called thin layers of phytoplankton in the ocean (Cowles et al 1998;Bochdansky and Bollens 2009;Sullivan et al 2010) are a type of DCM within which marine zooplankton have been shown to aggregate (Clay et al 2004;Ignoffo et al 2005) or visit for short-term feeding bouts Bochdansky et al 2010).…”
mentioning
confidence: 99%
“…The bottles were lit from the side to diminish vertical heterogeneity in the distribution of O. marina and C. typicus due to small-scale migrations during incubations ( Alcaraz et al. , 2007 ; Bochdansky et al. , 2010 ; Bollens et al.…”
Section: Methodsmentioning
confidence: 99%